Judd-Ofelt analysis in Yb3+Um3+Er3+Tridoped Teo2-Zno glass - Chacaliaza - Ricaldi, J. (2024)
The Judd-Ofelt analysis is essential becauseit indicates the influence of rare earth iondoping on the host matrix in which they arefound. In the present work, the results of theoptical characterization of zinc-tellurite glassesdoped with Yb3+ are presented, varying theconcentrations of Tm3+ and Er3+ by means of UVVISabsorption spectroscopy and refractive indexmeasurements. From these results, the Judd-Ofeltparameters were obtained, which indicated astructural modification with the addition of rareearth ions in the tellurite glassy matrix, due tothe rearrangement of the glassy structure and thebreaking of Te-O bonds.